2017
DOI: 10.1002/jssc.201700688
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast cell membrane chromatography coupled with liquid chromatography and time-of-flight mass spectrometry for screening specific active components from traditional Chinese medicines

Abstract: A method using osteoblast membrane chromatography coupled with liquid chromatography and time-of-flight mass spectrometry was developed to recognize and identify the specific active components from traditional Chinese medicines. Primary rat osteoblasts were used for the preparation of the stationary phase in the cell chromatography method. Retention components from the cell chromatography were collected and analyzed by liquid chromatography with time-of-flight mass spectrometry. This method was applied in scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Similar structure: protective effects against Alzheimer’s disease (Wang et al 2017a, b), antioxidant activity (Koo et al 2012), used to prevent and treat a disease caused by over activity of a liver X receptor α (LXR α) (Kim et al 2016), used for the treatment of skin pigmentation disorders (Commo and Michard 2009), neuroprotective activity (Jia et al 2009), act as cancer preventive agent (Tran et al 2009), antioxidant activity (Perez-Leal et al 2017), anti-inflammatory and anti-neurodegenerative activity (Jarrott and Williams 2016)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar structure: protective effects against Alzheimer’s disease (Wang et al 2017a, b), antioxidant activity (Koo et al 2012), used to prevent and treat a disease caused by over activity of a liver X receptor α (LXR α) (Kim et al 2016), used for the treatment of skin pigmentation disorders (Commo and Michard 2009), neuroprotective activity (Jia et al 2009), act as cancer preventive agent (Tran et al 2009), antioxidant activity (Perez-Leal et al 2017), anti-inflammatory and anti-neurodegenerative activity (Jarrott and Williams 2016)…”
Section: Resultsmentioning
confidence: 99%
“…Similar structure: free radical scavenging activity (Adil et al 2018), active component of Angelica sinensis (AS) herb, used as the blood-nourishing tonic (Chen et al 2017), anti-inflammatory activity (Tran et al 2018), antioxidant and antibacterial activity against Bacillus subtilis , Staphylococcus aureus , Escherichia coli , Pseudomonas aeruginosa , Klebseilla pneumonia , Agrobacterium tumefaciens and antifungal activity against Candida albicans , Mucor sp., Aspergillus flavus , Penicilium expansum (Ksouri et al 2017), neuroprotective effect on PC12 cells (Lu-Si et al 2017), used to treat bone diseases (Wang et al 2017a, b), prevents cancer by increase the oxygen release efficiency of Hb (Wang and Chen 2017), neuroprotective and anticancer effects against lung (A549), human colon carcinoma (HCT-8), and hepatocarcinoma (HepG2) cancer cell (Gong et al 2016)…”
Section: Resultsmentioning
confidence: 99%
“…The results from current studies have demonstrated that icariin could promote the proliferation and migration of various cells. For example, icariin was found to tremendously enhance the osteoblast proliferation and Col I level using membrane chromatography coupled with liquid chromatography and time-of-flight mass spectrometry ( 15 ). Icariin treatment increased the proliferation of human neural stem cells and the formation of neurospheres ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell membrane was prepared according to the previous literature with some modifications [21]. At first, the cultured osteoblast (5 × 10 7 ) was washed twice with normal saline solution by centrifuging at 15 000 rpm and 4°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%